Pengembangan Model Blended Learning Mata Kuliah Perencanaan Pembelajaran Teknologi Informasi Dan Komunikasi - Yamanto Isa (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2015)
This research aimed at developing blended learning of model, to producing a variety of instructional material that can be used in inccordance with the need of learning in helping the learning process. The research was in conducted at Baturaja University at major Technology of Education. The Research method was Research and Development (R&D) model development Dick and Carey and Model Depelopment Instruktional (MPI). The developmental process applied two kind of validation, they were expert and empirical validation. Emperical validation conducted three field, one-to-one learner treatment 3 students small group treatment which is cover 9 students, and large treatment 30 students. The research resulted that model purposed could be effective development of blended learning model.